2018
DOI: 10.1111/cas.13609
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D2 promotes disease progression of renal cell carcinoma through the induction of angiogenin

Abstract: A hallmark of clear cell renal cell carcinoma (ccRCC) is the presence of intracellular lipid droplets (LD) and it is assumed that phosphatidic acid (PA) produced by phospholipase D (PLD) plays some role in the LD formation. However, little is known about the significance of PLD in ccRCC. In this study, we examined the expression levels of PLD in ccRCC. The classical mammalian isoforms of PLD are PLD1 and PLD2, and the levels of both mRNA were higher at the primary tumor sites than in normal kidney tissues. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…[17][18][19]57 The level of PLD2 is increased in ccRCC compared with normal kidney and is correlated with stage, grade, and poor prognosis. 67 Although an in vitro study showed that PLD2 increases HIF-1a and HIF-2a at a translational level, 68 it is not clear if the effect of PLD2 on HIFs is mediated through LPA and its GPCRs. As an inhibitor of ATX prolongs sensitivity to sunitinib, 64 these findings suggest that LPA is a potential therapeutic target for RCC.…”
Section: Glycerophospholipid Metabolism In Rccmentioning
confidence: 99%
“…[17][18][19]57 The level of PLD2 is increased in ccRCC compared with normal kidney and is correlated with stage, grade, and poor prognosis. 67 Although an in vitro study showed that PLD2 increases HIF-1a and HIF-2a at a translational level, 68 it is not clear if the effect of PLD2 on HIFs is mediated through LPA and its GPCRs. As an inhibitor of ATX prolongs sensitivity to sunitinib, 64 these findings suggest that LPA is a potential therapeutic target for RCC.…”
Section: Glycerophospholipid Metabolism In Rccmentioning
confidence: 99%
“…Many studies now implicate phospholipase D (PLD) in tumorigenesis since total PLD activity and the expression of its two major isoforms PLD1 and PLD2 are elevated in many cancers where increases can correlate with prognosis. 1 8 Higher PLD activity is also linked to survival and migration signals in human breast cancer cells and in androgen-insensitive prostate cancer cell lines. 9 , 10 Selective inhibition of PLD1 or PLD2 also makes breast cancer cells more sensitive to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…MT1-MMP, tethered to the plasma membrane, is a key protein associated with the migration of cancer cells (67). PLD2 generates small lipid molecules, such as phosphatidic acid, which can regulate the movement of the cytoskeleton, proliferation and migration (68)(69)(70). Therefore, it has been suggested that PLD2 and its small lipid molecules can regulate MT1-MMP for invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%